2014 IEEE Antennas and Propagation Society International Symposium (APSURSI) 2014
DOI: 10.1109/aps.2014.6905358
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of a dual-loop FSS-based absorber

Abstract: In this paper, we investigate an approach to designing FSS-based absorbers with the objective of extending the bandwidth performance and absorption level. Numerical results are presented to illustrate the application of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Due to the characteristics of suppressing surface waves and reflecting with no phase reversal at a forbidden frequency, 8 dB in-band RCSR is reached. Recent researches indicated that metamaterials and matesurfaces come into sight with some superior performance [12][13][14][15][16][17][18][19][20][21][22][23]. Besides RCSR, metasurfaces have also been used for specific absorption rate reduction [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the characteristics of suppressing surface waves and reflecting with no phase reversal at a forbidden frequency, 8 dB in-band RCSR is reached. Recent researches indicated that metamaterials and matesurfaces come into sight with some superior performance [12][13][14][15][16][17][18][19][20][21][22][23]. Besides RCSR, metasurfaces have also been used for specific absorption rate reduction [12].…”
Section: Introductionmentioning
confidence: 99%
“…Three circular rings-shaped resonating elements with different radius were combined to gain three resonant frequencies absorption in [17]. The authors [18,19] investigated that resistively printed dual-loops and resistor-loaded conducting loops can extend the bandwidth and absorption level of the metamaterial absorber. An equivalent circuit model is also proposed to explain how the resonances can be produced and simple design guidelines have been developed for determination of parameter values.…”
Section: Introductionmentioning
confidence: 99%